The post COVID-19 green recovery in practice: Assessing the profitability of a policy proposal on residential photovoltaic plants. (December 2020) - D'Adamo, Idiano; Gastaldi, Massimo; Morone, Piergiuseppe
Abstract: The development of photovoltaic (PV) energy has been very significant in the last years, thanks to cost reductions brought about by policy actions favouring the transition from a fossil to a green society. As this transition is likely to stretch over the long term, policy support must be programmed accordingly. In light of the human and economic shock effected by COVID-19, the Italian government has offered a tax deduction of 110% over 5 years for the realization of new PV residential plants. We propose to integrate this tool with the application of a bonus for energy produced and self-consumed, in order to support the development of decentralized systems. In this paper, we provide an economic assessment of a 3 kW plant in the context of several policy scenarios. The results underline the great opportunity for consumers to tackle climate change whilst obtaining relevant economic profits. The study can be replicated on a global scale. Highlights: Tax deduction equal to 110% over a period of 5 years is investigated. A bonus for the energy self-consumed is proposed and analyzed. The adoption of the proposed policies can influence the economic results. The profitability of PV plants depends on the share of self-consumed energy. PV plants generate economic returns with low risk.